2020
DOI: 10.3390/f11020135
|View full text |Cite
|
Sign up to set email alerts
|

DBH Distributions in America’s Urban Forests—An Overview of Structural Diversity

Abstract: Background and Objectives: The structural diversity of an urban forest affects ecosystem service provision, and can inform management, planning, as well as policy. Trunk diameter at breast height (DBH) is amongst the most common measures of tree structure due to its ease of measurement and strong relationships with other structural and non-structural urban forest characteristics. Materials and Methods: In this study, the DBH distributions of urban forests are summarised for 38 American cities with a combined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
(53 reference statements)
2
10
0
8
Order By: Relevance
“…Out of four stem diameter classes, dominance of smaller diameter class (5-9.90 cm and 10-19.90 cm) in the urban stratum in the study area (Table 4) is similar as Morgenroth et al (2020) reported in America's urban forests as > 40% of trees in Shrestha et al the smallest DBH class (< 15 cm) which could be attributed to preference for smaller ornamental trees as Bottle brush, Albizia, Junipers etc. in urban areas or a recent increase in tree planting efforts.…”
Section: Market Value Of Merchantable Woodsupporting
confidence: 82%
“…Out of four stem diameter classes, dominance of smaller diameter class (5-9.90 cm and 10-19.90 cm) in the urban stratum in the study area (Table 4) is similar as Morgenroth et al (2020) reported in America's urban forests as > 40% of trees in Shrestha et al the smallest DBH class (< 15 cm) which could be attributed to preference for smaller ornamental trees as Bottle brush, Albizia, Junipers etc. in urban areas or a recent increase in tree planting efforts.…”
Section: Market Value Of Merchantable Woodsupporting
confidence: 82%
“…Natural tree regeneration and supporting their healthy development should also be a short-term goal in order to stop the ageing distribution from shifting toward maturity. The health of trees is improved through tree management, which also enhances the ecological functions and landscape services they offer (Morgenroth et al 2020). Tree health may be identified by the diversity of diameter distributions (Morgenroth and Östberg 2017;Pretzsch et al 2021).…”
Section: Vegetation Structurementioning
confidence: 99%
“…i-Tree is a software suite developed by the USDA Forest Service that provides urban and rural forestry analysis and benefit assessment tools. Since the initial release of i-Tree tools in 2006, this software has been widely used to quantify the benefits and values of individual trees and forests [27,28]. The most commonly used i-Tree tool is the i-Tree Eco model.…”
Section: I-tree Model Simulationmentioning
confidence: 99%